Game world generation based on geospatial data - Moura, Selthon Noronha de; Silva Junior, Jucimar Maia da; Araujo, Cristina Souza de (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Integrating geospatial data into digital games enables maps and environments that reflect real-world spatial structures. Instead of manually modeling terrain and cities, developers increasingly rely on datasets that describe geographic features such as roads, buildings, and terrain elevation. This trend is driven by improvements in game engines and geospatial data processing tools. Objective: To describe the main techniques and technologies used for generating maps in digital games based on real geospatial data. Methodology: This work was conducted through a review of academic literature and official documentation of widely adopted tools in the field. Aspects such as supported data formats, integration with game engines, licensing, and applicability were analyzed. Results: The survey identifies commonly adopted solutions and workflows in game development, along with legal and technical challenges related to data usage. It also highlights research opportunities in efficiently and creatively using spatial data in games.